Dissolution improvement of nebivolol hydrochloride using solid dispersion adsorbate technique - Shah, Mr. Harsh (Asian Journal of Pharmaceutics (AJP), 2015)
Nebivolol hydrochloride is unique antihypertensive drug, which gets completely absorbed upon oral administration,Â with tmax 1.5-4 h. The poor aqueous solubility leads to slow rate of absorption. An attempt has been made to enhanceÂ dissolution of nebivolol (NB) using solid dispersion (SD) and SD adsorbate (SDA) techniques.Various hydrophilic excipientsÂ such as polyethylene glycol 6000 (PEG), gelucire 50/13 (GL), and neusilin US2 (NUS) at different ratios were used. TheÂ prepared SDA of NB was characterized for % drug yield and other physical characteristics and in vitro drug dissolution studiesÂ in 0.1N HCl (pH 1.2). The formulation optimized on the basis of in vitro drug dissolution and % drug content was alsoÂ characterized by the Fourier transform infrared (FTIR) spectroscopy; differential scanning calorimetry (DSC), Xâ€ray powderÂ diffractometry analysis (XRD). The FTIR study indicated no interaction between the drug and polymer. DSC thermogramsÂ showed the significant change in melting peak of the NB when prepared as SDA suggesting the change in crystallinity of NB. The data from the XRD showed that the drug was still detectable in its solid state in the SDA of PEG and disappeared in case of higher ratio of GL. An increased dissolution rate of NB at pH 1.2 was observed when the drug was dispersed inÂ these carriers in the form of physical mixtures (PMs), SDs by solvent evaporation methods (SMs), SDs by fusion methodand SDAs by fusion method. NB released faster from the SDAs than from the pure crystalline drug, the PMs, the SMs, orÂ the SDs. Thus, this study was proved as a promising approach for the improvement of dissolution rate and solubility of NB. Key words: Antihypertensive drugs, physical mixture, solid dispersion, solid dispersion adsorbate